Cultural Literacy: Open-minded in Book Chapter 'Teacher Training, School Norms, and Teacher Effects' in Education of Indonesia Book - Bandan, Aldo Prabowo (Foremost Journal, 2022)
A liberal-arts education aims for open-mindedness, which falls under the more basic goals of transferring and expanding key areas of knowledge, laying the groundwork for democratic citizenship, and encouraging prolonged acquirement of intellectual. Open-mindedness is not something that is acquired through teaching, and it is not something that is normally engaged after much thought and decision-making (Adler, 2005). This study investigated in book chapter â€œTeacher Training, School Norms, and Teacher Effectsâ€ of Education of Indonesia book, used content analysis. The researcher revealed that values of open-minded, those are: Willingness 18, Ability to seek reasons and evidence 27, Matter of attitudes and technique 6, and Allow novel ideas and rival values 9. It results that combinations of willingness 30%, ability to seek reasons, and evidence 45%, matter of attitudes and technique 10%, and allow novel ideas and rival values 15%.